Pengaruh Sosialisasi Penerapan PP Nomor 23 Tahun 2018 terhadap Kepatuhan Wajib Pajak dengan Kesediaan Wajib Pajak sebagai Variabel Intervening - Vika Surya Widada (JURNAL ILMIAH EDUNOMIKA, 2021)
The purpose of this study is to determine the effect of the socialization of the application of PP number 23 of 2018 on taxpayer ompliance with the willingness of taxpayers as an intervening variable. This research was conducted on batik SMEs taxpayers in Bantul district. The number of samples in this study were 100 respondents with the sampling method using convenience sampling method. Data collection was carried out by distributing questionnaire. The data analysis technique used in this research is to use measurement model testing as well as structural model testing. Based on the results of the analysis, it can be seen that the socialization of the implementation of PP Number 23 of 2018 has a positive effect on taxpayer compliance with the willingness of taxpayers as an intervening variable.